Enhancing diets: A Nutrition Behaviour Change Strategy for Malaita, Solomon Islands - Nabuuma, Deborah; Ekesa, Beatrice (2025)
This Nutrition Behaviour Change Strategy (NBCS) was developed as a guide for nutrition interventions, activities, and communication within a nutrition-sensitive agriculture project in Solomon Islands. The NBCS was participatorily developed particularly for Malaita province but is also applicable to other provinces in the country. The aim of the NBCS is to improve diet quality among rural communities in Malaita, particularly women and children, by enhancing increased production and consumption of healthy sustainable diets from diverse locally available foods. The NBCS lays out the specific desired behaviours for different target groups, the key issues related to the behaviours, and the approaches that can be used to address the identified issues. The key messages that span across different approaches and activities suggested in the NBCS include: (1) Diversity – consume diverse diets that include all five main food groups (starchy staples, animal source foods, plant protein rich foods, fruits, and vegetables); (2) locally available – leverage the various food sources within the communities, including farms, stores, markets, and wild resources, to ensure access to a diverse and nutritious diet; and (3) value for money and nutrition – effectively use income to purchase foods that contribute to more diverse and balanced diets.